Oh, dude, 5 times 12 is like 60. It's basically like adding 12 five times or multiplying 5 by 12, whichever way you wanna look at it. So, yeah, 60.
Here is the work for that problem: 5x+ 2=12 5x= 12-2 5x=10 x= 2
17
To simplify the expression 18 + 7x - 12 + 5x, you first combine like terms. Combine the constants (18 and -12) to get 6. Then, combine the x terms (7x and 5x) to get 12x. Therefore, the simplified expression is 6 + 12x.
5x - 60 = 5*(x - 12)
x = 3
If that's -144, the answer is (5x + 12)(5x - 12)
2X2+5x-12 4+5x-12 -8+5x 5x-8
Here is the work for that problem: 5x+ 2=12 5x= 12-2 5x=10 x= 2
5x + 3 = -12 5x =-12-3 =-15 x = -3
(3)(2)(2)5x=60 12(5x)=60 12(5x)/12=60/12 5x=5 x=1
5x - 3 + x - 9 = 5x Bring like terms together of the left side: 5x + x - 3 - 9 = 5x Combine like terms: 6x - 12 = 5x Add 12 to both sides: 6x = 5x + 12 Subtract 5x from both sides: x = 12
-5x + 13 = -12 -5x = -12 - 13 = -25 x = -25/-5 = 5
To simplify the expression 18 + 7x - 12 + 5x, you first combine like terms. Combine the constants (18 and -12) to get 6. Then, combine the x terms (7x and 5x) to get 12x. Therefore, the simplified expression is 6 + 12x.
2x2 - 5x + 12 does not factor. 2x2 - 5x - 12 factors into (2x + 3)(x - 4) 2x2 + 5x - 12 factors into (2x - 3)(x + 4)
If you mean 5x+2 = 12 then 5x = 10 and the value of x is 2
It is 5x - 4
17